When the Values of Clients and Counsellors Clash: Some Conceptual and Ethical Propositions - Mitchell, Dan L. (Canadian Journal of Counselling and Psychotherapy, 1993)
This article addresses those difficult situations in counselling that are characterized by a fundamental clash in values between client and counsellor. A conceptual framework is offered for understanding the bases of fundamental value clashes, counsellor bias, counsellor integrity, and respect for clients. A model for ethical counselling concerning fundamental value clashes is presented. Of primary importance in the model are counsellor self-scrutiny and obtaining clients' informed consent regarding the values employed by the agency and/or the counsellor.